EDUKASI MANFAAT MASKER MADU DAN MINYAK ZAITUN UNTUK PENCEGAHAN JERAWAT TERHADAP KETUA KAMAR PUTRI PONDOK PESANTREN SALAFIYAH SYAFI’IYAH SUKOREJO SITUBONDO - Junaidah, Rini (Jurnal Pengabdian Masyarakat Berkarya, 2024)
Acne (Acne) is a type of skin health problem that is often found in teenagers. Acne can interfere with a person's appearance and can cause discomfort due to the pain it causes. Honey is an ingredient that contains high antioxidants. The antioxidant properties of honey are caused by various components in honey, including flavonoids, phenolics, vitamin C, amino acids. Olive oil contains very high levels of vitamin E, vitamin E itself functions to care for the skin so it is very suitable to be used as a mixture for acne removal masks. Antioxidant substances, as a mask mixture to soften the skin. Olive oil masks can be used to rejuvenate facial skin, or remove dead skin cells from acne scars. In contrast to external acne-removing cosmetics on the market, olive oil cannot remove acne scars directly, but requires patience to achieve maximum results, but of course it is safer than chemical-based cosmetics.